Determination of Carbonate Concentrations in Calcareous Soils with Common Vinegar Test - Qiang Zhu; Monica Ozores-Hampton; Yuncong Li (EDIS)
When raising crops on calcareous soils, growers need to know how much calcium carbonate is in the soil before they can employ any management practices. Growers can test the level of carbonate in their soils using store-bought vinegar and other household supplies. This 2-page fact sheet explains the chemistry behind the vinegar test and gives instructions for performing the test and interpreting the results. Written by Qiang Zhu, Monica Ozores-Hampton, and Yuncong Li, and published by the UF Department of Horticultural Sciences, June 2015.